Probing the Rotational Dynamics of meso‐(2‐Substituted)aryl Substituents in A2B‐Type Subporphyrins. Issue 32 (26th June 2014) - Yoshida, Kota; Copley, Graeme; Mori, Hirotaka; Osuka, Atsuhiro
Abstract A2B‐type B‐methoxy subporphyrins 3 a–g and B‐phenyl subporphyrins 7 a–c, e, g bearing meso‐(2‐substituted)aryl substituents are synthesized, and their rotational dynamics are examined through variable‐temperature (VT) 1H NMR spectroscopy. In these subporphyrins, the rotation of meso‐aryl substituents is hindered by a rationally installed 2‐substituent. The rotational barriers determined are considerably smaller than those reported previously for porphyrins. Comparison of the rotation activation parameters reveals a variable contribution of ΔH≠ and ΔS≠ in ΔG≠. 2‐Methyl and 2‐ethyl groups of the meso‐aryl substituents in subporphyrins 3 e, 3 f, and 7 e induce larger rotational barriers than 2‐alkoxyl substituents. The rotational barriers of 3 g and 7 g are reduced by the presence of the 4‐dibenzylamino group owing to its ability to stabilize the coplanar rotation transition state electronically. The smaller rotational barriers found for B‐phenyl subporphyrins than for B‐methoxy subporphyrins indicate a negligible contribution of SN1‐type heterolysis in the rotation of meso‐aryl substituents.